Local atomic disorder and temperature dependence of saturation magnetization in yttrium iron garnet. Issue 5 (1st April 2020) - Peña-Garcia, R.; Guerra, Y.; Oliveira, D.M.; Franco, A.; Padrón-Hernández, E.
Abstract: In the present work experimental data for saturation magnetization at low temperatures, of yttrium iron garnet nanoparticles are different from that expected by the T 3/2 Bloch's Law. This result is mainly conditioned by the local atomic disorder induced during the nanoparticles preparation by using the sol gel method. To correctly describe the experimental curves, a fitting using Cojocaru's theory was performed because the model uses geometric and other conditions in agreement with our experimental results. The magnetic ions localized at the nanoparticles surface, outside the crystalline periodicity, are the responsible by the saturation magnetization behavior presented here.